Willingness-to-pay to access Ingenol Mebutate Gel for Actinic Keratosis Treatment in the U.S. Setting - Michael Willis; Sandra Erntoft; Sofie Persson; Jenny M. Norlin; Ulf Persson (Journal of Health Economics and Outcomes Research)
**Background:** Currently available topical treatments for actinic keratosis (AK) adversely affect patients’ quality of life because of long treatment durations and long-lasting local skin reactions (LSRs), which may result in poor treatment adherence and patient outcomes. Ingenol mebutate gel, a recently introduced treatment for AK, is administered for 2 or 3 days, and LSR’s are predicable in onset and duration.